Well-suited for success - Coles, Diana Murphy, author; Coloradoan, publisher (Colorado State University. Libraries, 1998)
Article from The Coloradoan about Women's Suits exhibit at Gustafson Gallery. Includes images of suits in exhibit.
Full name of exhibit is Women's Suits: Transformations in Forms and Fabric, 1890-1991
Keywords: Fashion -- History; Fashion -- Exhibitions